Immersive and Interactive Simulator to Support Educational Teaching - Guimaraes, Marcelo de Paiva (2015)
Visualization and manipulation of a discipline's content integrated with educational planning can enhance teaching and facilitate the learning process. This paper presents a set of tools developed to explore educational content using a multi projection system with high immersion and interaction support for group learning and a support run on Internet browsers for individual learning. The objects visualized are enriched with multimedia content such as video, audio, and text and can be used in different educational proposals. In this work, these tools were populated with content for teaching computer architecture for computer undergraduate students.